2021
DOI: 10.3389/fphys.2020.572605
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-coding RNA MIAT Knockdown Prevents the Formation of Intracranial Aneurysm by Downregulating ENC1 via MYC

Abstract: Intracranial aneurysm (IA) is vascular enlargement occurred on the wall of cerebral vessels and can result in fatal subarachnoid hemorrhage when ruptured. Recent studies have supported the important role of long non-coding RNAs (lncRNAs) in IA treatment. This study identified functional significance of lncRNA myocardial infarction associated transcript (MIAT) in IA. Myocardial infarction associated transcript and ectodermal-neural cortex 1 (ENC1) expression was detected by reverse transcription quantitative po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“… Jayasooriya et al (2018) found that camptothecin enhanced MYC-mediated ERS and led to autophagy. In addition, Li et al (2020) proved that the downregulating MYC-mediated ENC1 could prevent IA formation. Correlation analysis showed the tight connectivity between ERS signature genes and nearby genes of regulatory regions.…”
Section: Discussionmentioning
confidence: 99%
“… Jayasooriya et al (2018) found that camptothecin enhanced MYC-mediated ERS and led to autophagy. In addition, Li et al (2020) proved that the downregulating MYC-mediated ENC1 could prevent IA formation. Correlation analysis showed the tight connectivity between ERS signature genes and nearby genes of regulatory regions.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, accumulated studies have documented many molecules involved in IA, such as long noncoding RNA myocardial infarction associated transcript (MIAT), 25 stromal cell-derived factor-1alpha (SDF-1α), 26 histone deacetylase 9 (HADC9), 27 and coenzyme Q10. 28 Using an IA-related microarray, we provided new insights into YAP1-dependent functions in IA.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we found significantly lower MIAT expression levels in MYC-translocated patients, and, accordingly, we found a significant enrichment of MYC targets in MM cases expressing MIAT at lower levels, thus suggesting a possible relationship between MIAT and MYC in MM. Studies in solid tumors [ 30 , 31 , 32 ] and other pathological conditions [ 33 , 34 ] have already described an interplay between MIAT and MYC family genes based on different regulation mechanisms, suggesting that this relationship may depend on the cellular context. Further studies are needed to clarify the relationship in MM.…”
Section: Discussionmentioning
confidence: 99%